2019
DOI: 10.4274/bmb.galenos.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume Values and Its Effects on Prognosis in Patients with Acute Ischemic Stroke

Abstract: Stroke is a rapid onset of focal or global loss of cerebral function and is the most common cause of mortality and morbidity in adulthood cancer and heart disease patients. Although it has been reported that mean platelet volume (MPV) values may be an independent risk factor for the severity and prognosis of stroke, the results of previous studies are inconsistent. The aim of the present study was to determine the MPV values of ischemic stroke patients which reflects the activity and function of platelets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…However, there is no consensus in the literature about the correlation between MPV and cardiovascular diseases. For example, some studies found an association between a high MPV level and the risk of stroke [22][23][24], while others could not [15]. MPV levels were high in patients with arrhythmogenic right ventricular cardiomyopathy or dysplasia (ARVC/D) [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus in the literature about the correlation between MPV and cardiovascular diseases. For example, some studies found an association between a high MPV level and the risk of stroke [22][23][24], while others could not [15]. MPV levels were high in patients with arrhythmogenic right ventricular cardiomyopathy or dysplasia (ARVC/D) [17].…”
Section: Discussionmentioning
confidence: 99%